OVERVIEW OF DIABETES MELLITUS CASES IN THE COMMUNITY OF KRUENG SABE SUBDISTRICT, ACEH JAYA REGENCY - Bancin, Indah Sari; Kala, Pasyamei Rembune; Mustafa, Ns. Diana (Transpublika Publisher, 2023)
This quantitative descriptive study aimed to characterize diabetes mellitus (DM) cases in Alue Tho Village, Krueng Sabe Subdistrict, Aceh Jaya Regency. A sample of 75 out of 108 families was surveyed over one month to assess community health, including Clean and Healthy Living Behavior (PHBS) behaviors, associated factors, and potential intervention strategies. Data collection involved structured interviews and questionnaires, ensuring respondent confidentiality. Descriptive statistics were used to analyze Clean and Healthy Living Behavior (PHBS) behaviors and compare characteristics of individuals with and without DM. The age group of 41-50 years constituted the largest proportion in both groups. Identified health factors such as hypertension, smoking, diet, physical activity, cholesterol, stroke, and heart disease provide valuable insights for developing effective DM management programs in the region. The surveillance of DM cases in Krueng Sabe Subdistrict, Aceh Jaya District, reveals that the demographic distribution of DM is significantly influenced by age and gender. The highest prevalence of DM cases is observed in the 51-60 age group. Despite low proportions of risk factors like smoking and high cholesterol levels, the respondents showed an awareness of healthy living through their vegetable/fruit consumption and participation in physical activities. Notably, no cases of stroke or heart disease were reported among the DM respondents in this surveillance.